Tax decentralization notwithstanding regional disparities - Antonio Andrés Bellofatto; Martin Besfamille (Center for Economic Studies and ifo Institute (CESifo), 2019)
In assessing the desirability for tax decentralization reforms, a dilemma between efficiency and redistribution emerges. By limiting the ability of the central government to redistribute resources towards regions in financial needs, decentralization curbs incentives for excessive subnational spending and enhances fiscal discipline, but may also widen interregional disparities by triggering tax competition for mobile tax bases. We provide a formal treatment of this trade-off, and shed light on the optimal degree of fiscal decentralization. We find that tax decentralization can be optimal even under Rawlsian social preferences which only weight the welfare of the poorest region in the federation.
Keywords: H77; 330; fiscal federalism; tax competition; regional disparities